PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIIVITAS KERJA KARYAWAN PT PLN (PERSERO) UPDK BAKARU - Musdalifah, Musdalifah; Rika Rahma (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study was to analyze the effect of work discipline and work environment on employee productivity. The population in this study were employees of PT. PLN (Persero) UPDK Bakaru. Determination of the research sample using a saturated sampling technique, namely the total population. The sample in this study amounted to 71 respondents. The data collection techniques in this study were observation, questionnaires, and documentation. To apply these objectives, descriptive methods were used, prerequisite analysis with the help of a computerized system (SPSS version 24 computer program) using the formula, namely multiple regression analysis, t-test, and F test. The results showed that the variables of work discipline and work environment had a positive and significant effect on employee productivity at PT. PLN (Persero) UPDK Bakaru. The most dominant variable influencing the work productivity of employees at PT. PLN (Persero) UPDK Bakaru is a work environment that has the largest regression coefficient value when compared to the work discipline variable.